2008
DOI: 10.1016/j.optcom.2008.05.048
|View full text |Cite
|
Sign up to set email alerts
|

Absorption free superluminal light propagation in a three-level pump–probe system

Abstract: We investigate the dispersion and the absorption properties of a weak probe field in a three-level pump-probe atomic system. It is shown that the slope of dispersion changes from positive to negative just with the intensity of the coherent or indirect incoherent pumping fields. It is demonstrated that the absorption free superluminal light propagation is appeared in this system. Keywords: quantum coherence, susceptibility, group velocity Propagation of electromagnetic pulse in a dispersive medium has been a to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…The decay rates from level |3 to the ground levels |1 and |2 are given by γ 1 and γ 2 , respectively. The density matrix equations of motion in the rotating wave approximation and in the rotating frame are [65] …”
Section: Doppler Broadened Electromagnetically Induced Transparencymentioning
confidence: 99%
“…The decay rates from level |3 to the ground levels |1 and |2 are given by γ 1 and γ 2 , respectively. The density matrix equations of motion in the rotating wave approximation and in the rotating frame are [65] …”
Section: Doppler Broadened Electromagnetically Induced Transparencymentioning
confidence: 99%
“…These studies have found many applications, e.g. in electromagnetically induced transparency [20][21][22], electromagnetically induced absorption [23][24], laser without inversion [25,26], AutlerTownes effect [27][28][29], sub and super-luminal effects [30][31][32], optical bistability [33], entanglement [34], photons counting [3][4][5][6] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Slow and fast light propagation in solids at room temperature have also been realized based on the process of coherent population oscillations [5,6] and by using stimulated Brillouin scattering [7]. The absorption-free superluminal light propagation has been introduced in a closed-loop atomic system beyond multi-photon resonance condition [8] and in a three-level pump-probe system [9]. More recently, the gain-assisted superluminal pulse propagation via fourwave mixing in superconducting phase quantum circuits has been reported [10].…”
Section: Introductionmentioning
confidence: 99%